Pengaruh Jumlah Sekat Aliran Lapisan Pengisi Terhadap Unjuk Kerja Menara Pendingin (Cooling Tower) - Sumarjianto; Rubiono, Gatut; Qiram, Ikhwanul (Virtual of Mechanical Engineering Article, 2020)
The cooling tower has a working principle for cool the water fluid forcibly using a fan or blower. This Research aims to determine the effect of the number of filler bulkheads and the angle of openingvalve to the cooling tower work efficiency. This research uses type induced draft cooling tower with flow opposite the tool size laboratory scale. Research variables include 3 variations in the number of bulkheads (2 bulkheads, 3 bulkhead and 4 bulkheads) and 3 variations of valve opening angles (30, 45 and 60). Result measurements in the form of water discharge data, water temperature data, air temperature data, temperature data environment (Twb) and temperature difference data. Water discharge data is measured with a flow meter and stop watch. Temperature data measured with a Digital Thermometer. Data were collected 5 times repetition of each data. The measurement results are taken the average value for measures the discharge, temperature, heat transfer rate and efficiency of the cooling tower. The results showed that the number of bulkheads and the angle of the opening valve has an effect on the working efficiency of Cooling Tower which is getting more the greater the number of bulkheads the greater the cooling tower work efficiency and vice versa but the greater the valve opening angle the smaller the cooling tower efficiency.The maximum efficiency obtained from this study is at the number of bulkheads 4 and the valve opening angle of 30 with a Cooling Tower efficiency value of 78.40%.